2020
DOI: 10.2174/1871529x19666190222182312
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Lowering Activity of Aqueous Ammodaucus leucotrichus Extract in Diabetic Rats

Abstract: Background: Ammodaucus leucotrichus (Apiaceae) is a medicinal plant widely used by the Moroccan population to treat various diseases including diabetes. Aims: The aim of this study was to evaluate the antidiabetic effect of the aqueous extract prepared from the fruits of this medicinal plant. Normal and streptozotocin-induced diabetic rats were treated orally by the extract of Ammodaucus leucotrichus (A. leucotrichus) at a dose of 10 mg/kg. Methods: The blood glucose levels were determined during 6 hours a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Blood glucose was significantly reduced after 15 days of oral administration of the plant extract at a dose of 10 mg/kg. In addition, Ammodaucus leucotrichus fruit aqueous extract was able to exhibit a beneficial effect on histologlogical structure of liver and a remarkable influence on glucose tolerance [26].…”
Section: Antidiabetic Activitiesmentioning
confidence: 96%
See 2 more Smart Citations
“…Blood glucose was significantly reduced after 15 days of oral administration of the plant extract at a dose of 10 mg/kg. In addition, Ammodaucus leucotrichus fruit aqueous extract was able to exhibit a beneficial effect on histologlogical structure of liver and a remarkable influence on glucose tolerance [26].…”
Section: Antidiabetic Activitiesmentioning
confidence: 96%
“…Required concentrations to neutralize and stabilize 50% of DPPH concentration goes from 2 to 4 μg/ml [5]. A potential antioxidant effect of the aqueous extract from the fruits of Ammodaucus leucotrichus has been shown, in vitro, by the method of trapping of free radical 2,2-diphenyl-1 picrylhydrazyl [26].…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the data obtained showed that the age of the respondents varied between 22 and 80 years, with a majority of the age group [41][42][43][44][45][46][47][48][49][50] at 34%. Then come the age groups [51][52][53][54][55][56][57][58][59][60], [31][32][33][34][35][36][37][38][39][40], [21][22][23][24][25][26][27][28][29][30] and finally those over 61, with a rate of 26%, 18.7%, 11.3% and 10% respectively.…”
Section: Demographic Featuresmentioning
confidence: 99%
“…The leaves and seeds are used in the form of decoction or infusion for several therapeutic cases, such as blood pressure, chest pain, liver and digestive system ailments, gastroenteritis, as also for diabetes (Ziani et al, 2019). Furthermore, a pharmacological study realized showed that A. leucotrichus fruits had a significant effect on diabetes (El-Ouady and Eddouks, 2019). Currently, no study has been carried out on its action mechanisms.…”
Section: Introductionmentioning
confidence: 99%